Próba analizy porównawczej litewskiej gospodarki folwarczno-pańszczyźnianej i latynoamerykańskiej gospodarki hacjendowej od II połowy XVIII do II połowy XIX wieku w kontekście kapitalistycznego systemu-świata - Darius Žiemelis, Darius Žiemelis (Człowiek i Społeczeństwo, 2016)
The paper for the first time in historiography compares the Lithuanian manorial-serf economy and Latin American hacienda economic systems in the second half of the 18th century – the second half of the 19th century in the context of the capitalist world system (CWS). The main focus will be on the explication in macro level of similarities and differences of structures and development trends of these systems. The analyzed period – is the stage of both the dominance and intensification of manorial-serf economy in Lithuania and predominance and intensification of hacienda economy in Latin American countries and it was determined by the same factor of the industrial revolution. The study confirms the thesis that these economic systems belonged to typologically close economic type (were focused on the serfdom method of production) in the global division of labor. It shows that both Lithuanian manorial-serf economy and haciendas of Latin America were not typical feudal enterprises, but had only peripheral capitalism features.